Multi-agent and Complex Systems - Bai, Quan.; Ren, Fenghui; Fujita, Katsuhide; Zhang, Minjie; Ito, Takayuki; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book provides a description of advanced multi-agent and artificial intelligence technologies for the modeling and simulation of complex systems, as well as an overview of the latest scientific efforts in this field. A complex system features a large number of interacting components, whose aggregate activities are nonlinear and self-organized. A multi-agent system is a group or society of agents which interact with others cooperatively and/or competitively in order to reach their individual or common goals. Multi-agent systems are suitable for modeling and simulation of complex systems, which is difficult to accomplish using traditional computational approaches.
1.Adaptive Forwarder Selection for Distributed Wireless Sensor Networks -- 2.Trust Transference on Social Exchanges among Triads of Agents Based on Dependence Relations and Reputation -- 3.A Multiagent-Based Domain Transportation Approach for Optimal Resource Allocation in Emergency Management -- 4.A proto-type of a portable ad hoc simple water gauge and real world evaluation -- 5.Exploiting Vagueness for Multi-Agent Consensus 6.Selecting Robust Strategies Based on Abstracted Game Models -- 7.Simulating and Modeling Dual Market Segmentation Using PSA Framework -- 8.CORPNET: Towards a Decision Support System for Organizational Network Analysis using Multiplex Interpersonal Relations -- 9.Membership Function Based Matching Approach of Buyers and Sellers Through a Broker in Open E-Marketplace -- 10.The Effect of Assertiveness and Empathy on Heider's Balance Theory for Friendship Network Models information on submission -- 11.Associative Memory-based Approach to Multi-task Reinforcement Learning under Stochastic Environments -- 12.Preliminary Estimating Method of Opponent's Preferences using Simple Weighted Functions for Multi-lateral Closed Multi-issue Negotiations -- 13.Multi-Objective Nurse Rerostering Problem -- 14.Preference Aware Influence Maximization -- 15.Norm Emergence through Collective Learning and Information Diffusion in Complex Relationship Networks -- 16.Agent-Based Computation of Decomposition Games with Application in Software Requirements Decomposition.
Keywords: Dynamics; Nonlinear theories; Artificial intelligence; Computational intelligence; Computer networks .; Economic sociology; Applied Dynamical Systems; Artificial Intelligence; Computational Intelligence; Computer Communication Networks; Economic Sociology